Jungck-type Fixed Point Theorem in 0-complete Partial bv(s)-Metric Spaces: Muhammad Sirajo Abdullahi, Phumin Sumalai, Dhananjay Gopal, Poom Kumam - Team, Support (Thai Journal of Mathematics, 2020)
We present a variant of Jungck common fixed point theorem in a new and more generalized space, namely; 0-complete partial bv(s)-metric space and deduce some well-known results as corollaries. We also give some an illustrative example to support our results.